The Transition from Task Taker to Co-Designer in Dialogic CLIL Speaking: Students’ Perspectives - Aflahatun, Nur; Mujiyanto, Januarius; Fitriati, Sri Wuli; Pratama, Hendi (Journal of Education Reseach and Evaluation, 2025)
This study was motivated by a lack of understanding of how students experience the role transition from task taker to co-designer in a dialogic CLIL learning context. This study investigated civil engineering students' perceptions of their challenges in dialogic speaking tasks within a CLIL (Content and Language Integrated Learning) context. Using an explanatory sequential mixed methods design, data were collected through closed ended questionnaires from 32 participants, open ended questionnaires from 8 selected participants, and in-depth interviews with 3 participants. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed through thematic analysis. Findings revealed key challenges faced by students, including the need for clearer instructional support, emotional anxiety, technical difficulties, and linguistic barriers. Students reported a moderate need for more explicit guidance and examples, with anxiety emerging as the most significant affective challenge. Technical issues, such as difficulties in recording and uploading assignments and time management, were also identified as barriers to effective participation. This study emphasizes the importance of providing appropriate scaffolding, emotional support, and improving technical facilities to enhance student engagement. In conclusion, active student engagement as co-designers in dialogic CLIL practices encourages a shift in students' roles from mere task implementers to reflective and collaborative participants. Integrating quantitative and qualitative insights in this study provides important implications for educators, highlighting the need for deliberate task design and tailored support to foster student agency and facilitate deeper learning outcomes in dialogic CLIL environments.